Cancer screening. Issue 12 (1st December 2002) - Barratt, A; Mannes, P; Irwig, L; Trevena, L; Craig, J; Rychetnik, L
Abstract : "Screening is the systematic application of a test or inquiry, to identify individuals at sufficient risk of a specific disorder to benefit from further investigation or direct preventive action, among persons who have not sought medical attention on account of symptoms of that disorder." 1